Pengembangan Instrumen Deteksi Kemunduran Bio, Psiko, Sosio, Spiritual pada Pasien Lanjut Usia - Dewi, Nelly Hermala; Yupartini, Lisnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to develop an instrument that detects bio, psycho, social, and spiritual decline in elderly hospital patients by using theoretical concepts in nursing care. The research method uses cross-sectional, with validity and reliability tests using the Product Moment correlation test. The research results show that the bio, psycho, social, and spiritual deterioration detection instrument consists of 26 questions with high validity and reliability. This instrument has been based on various concepts that focus on the individual's bio, psychological, social, and spiritual needs. In conclusion, this instrument is easy to use and is an evidence-based nursing assessment tool. Keywords: Bio-Psycho-Socio-Spiritual Decline; Elderly Patients